Electronic Spectral Studies of Pr3+ Doped Sulphonanilide Systems, Part I - Tater, P.C.; Aryamitra Pandey, Ms.; Soni, K.P. (Asian Journal of Chemistry, 2010)
Twelve sulphonanilide ligands have been synthesised and their interaction with Pr3+ ion in the doped model form has been discussed in terms of Slater-Condon, Lande and Judd-Ofelt parameters. The involvement of 4f orbitals in the Pr3+ systems including deviation in symmetry have been discussed.